The influence of performance management and employee development on employee satisfaction at PT Plastic Injection Indonesia - Nabia Shalwa Bahtera Sudarjat; Era Era Hia; Temmy Setiawan (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to analyze the influence of performance management and employee development on employee satisfaction at PT Plastic Injection Indonesia. The phenomenon underlying this study is the importance of maintaining job satisfaction to improve productivity in the competitive plastic manufacturing industry. This study employs a quantitative approach using a survey method. The population in this study consists of 25 production department employees at PT Plastic Injection Indonesia, with a total sampling technique used to select 25 respondents. Data were collected through the distribution of questionnaires that had been tested for validity and reliability. The data analysis technique used was multiple linear regression analysis with the aid of statistical software. The validity test results indicate that all items in the performance management, employee development, and employee satisfaction variables have values exceeding the r-table, thus being declared valid. The reliability test using Cronbach’s alpha indicates that the entire study is reliable. Multiple linear regression analysis shows that performance management has a negative and significant effect on employee satisfaction. Performance management has a smaller beta coefficient than employee development, meaning that performance management does not have a greater influence on employee satisfaction than employee development. The F-test shows that, simultaneously, performance management